Optimization of the friction factor and frictional pressure drop of R22 and R290 - Mohd. Ghazali, Normah (2015)
Today, the air-conditioning and refrigeration industry is still searching for the environmentally friendly refrigerants that could replace the hazardous coolants that are ozone depleting – refrigerants that behave similarly, if not better than the present ones. The present study includes optimization of the frictional pressure drop of R22 and R290 using genetic algorithm. Parametric analysis have been conducted in order to determine the difference in the case of the use of genetic algorithms. The outcomes are compared against that of the measured pressure drop, the latter obtained from a horizontal 7.6 mm channel with a length of 1.07 meter. Three equations have been used for calculating the Darcy friction factor and two-phase flow pressure drop for both laminar and turbulent flow regimes in smooth and rough tubes. The effects of the different correlations for the friction factor and the pressure drop utilized are demonstrated. The results illustrate that the differences between values of the Darcy friction factor are very small for the two refrigerants, and the frictional pressure of R-290 higher than R-22. Smaller channel induced much higher frictional pressure drop too.